Análise da viabilidade econômica de sistemas de recuperação de pastagens degradadas em solos arenosos - Verdi, Paulo Henrique Peres (2018)
There is much talk about the low productivity of Brazilian cattle ranching and the enormous extent of degraded pastures that the country has, including regions of sandy soils with less agricultural potential. Public and private institutions invest in research to find alternatives on how to increase productivity and mitigate the environmental impacts caused by cattle production. The objective of this study is to analyze the economic viability of pasture recovery systems in sandy soils, considering the model of production in degraded pastures, the production model with the São Mateus integrated system, and a model considering pasture renovation and maintenance with fertilizers and correctives. From the main models, alternative scenarios have been created modifying the main variables to understand under which condition a system is economically attractive or not. The results indicate that the São Mateus integrated system is the most profitable in the proposed scenario, followed by the production model in degraded pastures. The model considering renovation of pastures on sandy soils with fertilization and maintenance of fertility resulted to be economically unfeasible.